2019
DOI: 10.21061/jvs.v4i2.102
|View full text |Cite
|
Sign up to set email alerts
|

Student-Veterans’ Perceptions of Barriers, Support, and Environment at a High-Density Veteran Enrollment Campus

Abstract: For institutions of higher education with high numbers of enrolled veterans, understanding how these students perceive services specifically designed for them is an important next step in developing effective campus service models. Through analysis of survey data (n=328) collected at a campus with a host of established services and a high number of military connected students, this study adds to the literature on the transition experience and utilization of resources. This investigation focuses on the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…Other articles presented a pervasive expectation that the SMB would seek help on their own accord if resources were available (Cox, 2019;Shellenberger & Decker, 2019;Williams-Klotz & Gansemer-Topf, 2017). Similar to other studies our SMB indicated they preferred to seek help from faculty with whom they were familiar and also indicated interest in developing a faculty-mentoring program for student veterans (Morris et al, 2019;Williams-Klotz & Gansemer-Topf, 2017). These findings suggest these SMB have an overall positive relationship with faculty in the learning environment of this academic medical center campus.…”
Section: Learning Experiencessupporting
confidence: 78%
See 2 more Smart Citations
“…Other articles presented a pervasive expectation that the SMB would seek help on their own accord if resources were available (Cox, 2019;Shellenberger & Decker, 2019;Williams-Klotz & Gansemer-Topf, 2017). Similar to other studies our SMB indicated they preferred to seek help from faculty with whom they were familiar and also indicated interest in developing a faculty-mentoring program for student veterans (Morris et al, 2019;Williams-Klotz & Gansemer-Topf, 2017). These findings suggest these SMB have an overall positive relationship with faculty in the learning environment of this academic medical center campus.…”
Section: Learning Experiencessupporting
confidence: 78%
“…PTS has been linked to academic difficulties including memory skills, organizing study habits, completing homework, and attending class. Service-related physical limitations present challenges navigating the campus (Morris et al, 2019;Morissette et al, 2019) or accessing course content. Sensory impairments in particular present difficulties with following in-class lectures, interpreting visual aids used during lectures, and completing reading assignments.…”
Section: Smb Learning Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…By utilizing NVivo's word frequency query search, three topics emanate from the theme of student veterans as observed in JVS articles. They are student veteran transition experiences from military to civilian and becoming student veterans (Andrewartha & Harvey, 2019;Bodrog et al, 2018;Boettcher et al, 2017;Jenner, 2017;McMenamin, 2016;Mendez et al, 2018;Petri et al, 2016;Phillips, 2016;Pollak et al, 2019;Young, 2017), conditions surrounding student veteran academic success (Bagby et al, 2019;Blackwell-Starnes, 2018;Cipher et al, 2018;Flatt & Rhodes, 2019;Garrity, 2017;Hembrough, 2017;Hembrough et al, 2018;Spencer, 2016), and issues surrounding accommodations needed by student veterans (Flink, 2017;Kranke et al, 2017;Morris et al, 2019;Wild & Mahapatra, 2018).…”
Section: Themes From Jvs Articlesmentioning
confidence: 99%
“…Research on student veterans has steadily increased over the years. Many studies have taken into account how student veterans interact with their collegiate environment both inside and outside of the classroom (Ackerman et al, 2009;Bryan et al, 2014;Campbell & Riggs, 2015;DiRamio et al, 2008;Kirchner, 2015;Morris et al, 2019;Nyaronga & Toma, 2015;Romero et al, 2015;Vaccaro, 2015;Wheeler, 2012;Williams-Klotz & Gansemer-Topf, 2017), but a limited number of scholars have examined how this population comes to develop an internal veteran identity. The topic of veteran identity has received increased attention in the past few years (Blackwell-Starnes, 2020;Hinton, 2020), yet is still an area needing additional research.…”
mentioning
confidence: 99%